Digital cervical cancer screening: a reliable One-Stop method ? - Al-Mehaisen, Lama; Al-Shatanawi, Tariq; AL-Husban, Naser; Albeitawi, Soha; Hiasat, Duaa; AL-Kuran, Lena; Al-Kuran, Oqba (Jordan Medical Journal, 2022)
Background Worldwide, cervical cancer (CC) is considered the fourth most common cancer in women. Globocan data stated 311,365 CC related mortalities in the world in 2018, 90% of them occurred in low-income countries. In Jordan, CC ranks as the 12th most common cancer among women. The primary aim of this report is to be able to decide if digital screening (DS) is reliable and worth using in our one stop gynecology clinics. Materials and Methods This study was done for all women who attended one stop out-patient gynecology services for routine CC screening between 1/1/2019 and 31/12/2019. Inclusion criteria requested women to be 18 years of age or more, healthy, and had previously normal cervical smear (conventional Pap smear (CPS) or Liquid based cytology (LBC)) i.e., all previous screening tests results were normal. Results A total number of 94 patients agreed to have the DS method done, mean age was 43 years. 25.5% were found to have abnormal screening results on DS. When compared to the national data of 12.5% abnormal smears in Liquid‐based cytology (LBC), there was a statistically significant difference in the numbers of abnormal screening results between both methods (p value of 0.000). LBC is used in most centers for CCS in Jordan Conclusion The digital cervical screening method saves time and offers a one stop clinic management, therefore minimizing lost to follow up rate, and where colposcopy is indicated. Additionally, DS should be considered in low resource countries.